The biomechanics Analysis of the Suitability of Horse Kicking for Junior Athletes in the Single Arts Category Jepara Regency - Billah, Tafriyadhur Risa; Rahayu, Setya; Irawan, Fajar Awang; Setiawan, Ipang (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2023)
This study aims to determine the suitability of the movement of horse kicks which is one of the movements that is considered to have the highest artistic beauty, horse kicks are considered to have a high level of difficulty compared to other movement techniques. horse kick is an attack in the art category that is effective for generating high points. The type of research used is quantitative descriptive analysis using the observation method. The sample for this study was athletes in the junior singles arts category in Jepara district, totaling 10 athletes. This study used data analysis techniques using Kinovea software version 0.9.5. Based on the results of the motion suitability analysis in the implementation phase, stages one to 3 obtained an average of 2.12. The results of this study indicate that all horse kick movement indicators are included in the "appropriate" criteria. There needs to be a significant improvement and increase in movement by using guidelines that are in accordance with the applicable rules in order to get maximum movement and fall into the very appropriate category, through improving the performance movement to the maximum so that it is worth competing in and preventing mistakes that risk causing injury to athletes.